(untitled) - Gibson, Walton C. (Boca Raton, 2008)
Responding to the need for a clear, up-to-date introduction to the field, The Method of Moments in Electromagnetics explores surface integral equations in electromagnetics and presents their numerical solution using the method of moments (MOM) technique. It provides the numerical implementation aspects at a nuts-and-bolts level while discussing integral equations and electromagnetic theory at a higher level. Subsequent chapters solve these integral equations for thin wires, bodies of revolution, and two- and three-dimensional problems. The final chapters examine the contemporary fast multipole method and describe some commonly used methods of numerical integration, including the trapezoidal rule, Simpson’s rule, area coordinates, and Gaussian quadrature on triangles. The text derives or summarizes the matrix elements used in every MOM problem and explains the approach used in and results of each example. This book provides both the information needed to solve practical electromagnetic problems using the MOM and the knowledge necessary to understand more advanced topics in the field.
Keywords: Electromagnetism,Electromagnetic fields,Moments method (Statistics),Lý thuyết từ trường; Data processing,Mathematical models,Điện từ học